2018
DOI: 10.12793/tcp.2018.26.1.25
|View full text |Cite|
|
Sign up to set email alerts
|

Population pharmacokinetic analysis of metformin administered as fixed-dose combination in Korean healthy adults

Abstract: Metformin, an oral antihyperglycemic agent, is widely used as the first-line pharmacotherapy for type 2 diabetes mellitus (T2DM). It has been in use for several decades as numerous different formulations. However, despite its use, population pharmacokinetic (PK) modeling of metformin is not well developed. The aim of the present study was to evaluate the effect of formulation on PK parameters by developing a population PK model of metformin in Koreans and using this model to assess bioequivalence. We used a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Nonetheless, Cvijic et al summarised that metformin absorption appears to be quite complex, which is characterised by saturable paracellular and transcellular pathways 20 . In fact, recent population PK studies on metformin showed that metformin absorption is better described by complex models such as first‐order absorption followed by zero‐order absorption with lag time 28 or two separate absorption pathways to account for different absorption sites in the gastrointestinal tract 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, Cvijic et al summarised that metformin absorption appears to be quite complex, which is characterised by saturable paracellular and transcellular pathways 20 . In fact, recent population PK studies on metformin showed that metformin absorption is better described by complex models such as first‐order absorption followed by zero‐order absorption with lag time 28 or two separate absorption pathways to account for different absorption sites in the gastrointestinal tract 29 …”
Section: Discussionmentioning
confidence: 99%
“…Dashed red lines are predicted median, 5th and 95th percentiles. Blue shaded areas represent 95% confidence intervals around predicted percentiles studies on metformin showed that metformin absorption is better described by complex models such as first-order absorption followed by zero-order absorption with lag time 28 or two separate absorption pathways to account for different absorption sites in the gastrointestinal tract. 29 In our earlier attempt to fit metformin data with the transit compartment model, we noticed that Savic et al used Stirling's approximation to n!…”
Section: Discussionmentioning
confidence: 99%
“…Metformin formulations were also assessed for their bioequivalence by developing a population PK model using NONMEM ® based on comparative PK study of a single agent and a fixed-dose combination of metformin in 36 healthy Korean volunteers. It was found to be best described by a two-compartment model, first-order elimination with two absorption processes separated by a lag time [59]. The study, however, concluded that actual clinical trials should be conducted and that simulations would be useful only to identify possible differences in formulations.…”
Section: Nonmem ®mentioning
confidence: 99%
“…In addition, a study showed that the OCTN1-917C > T gene variant and the OCT2-808 G > T gene polymorphism can be used to determine the optimal dose of metformin. All the models were internally validated by a visual predictive check (VPC) [18][19][20][21][22][23], normalized prediction distribution error (NPDE) [19,24], boot-strap analysis [18][19][20][21][23][24][25], diagnostic plots [18][19][20][21][23][24][25][26][27], and the prediction error test [23,28]. In terms of pharmacokinetic parameters, except for studies in special populations, CL/F is basically between 50-80 l/h (Figure 2).…”
Section: Study Identificationmentioning
confidence: 99%